2014
DOI: 10.1016/j.ejpb.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of co-delivery of paclitaxel and curcumin by transferrin-targeted PEG-PE-based mixed micelles on resistant ovarian cancer in 3-D spheroids and in vivo tumors

Abstract: Multicellular 3D cancer cell culture (spheroids) resemble to in vivo tumors in terms of shape, cell morphology, growth kinetics, gene expression and drug response. However, these characteristics cause very limited drug penetration into deeper parts of the spheroids. In this study, we used multi drug resistant (MDR) ovarian cancer cell spheroid and in vivo tumor models to evaluate the co-delivery of paclitaxel (PCL) and a potent NF-κB inhibitor curcumin (CUR). PCL and CUR were co-loaded into the polyethylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 107 publications
(133 reference statements)
0
74
0
1
Order By: Relevance
“…linoleic acid -LNA, palmitic acid -PAC, and oleic acid -OA) allows the obtainment of CUR delivery nanocarriers suitable for the treatment of cervical (Sahu et al, 2008a;Song et al, 2014), brain (Erfani-Moghadam et al, 2014, and lung tumors (Erfani-Moghadam et al, 2014), with superior efficiency and pharmacokinetics (Song et al, 2014). A different approach involves the employment of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] in a thin-layer evaporation methods for the preparation of CUR micelles able to treat ovarian Sarisozen et al, 2014) and colon (Abouzeid et al, 2013) cancer cells in vitro and in vivo (Abouzeid et al, 2013;Sarisozen et al, 2014), conferring synergistic effect to PTX- and DOX- (Abouzeid et al, 2013) based therapies.…”
Section: Polymeric Vesicular Systemsmentioning
confidence: 99%
“…linoleic acid -LNA, palmitic acid -PAC, and oleic acid -OA) allows the obtainment of CUR delivery nanocarriers suitable for the treatment of cervical (Sahu et al, 2008a;Song et al, 2014), brain (Erfani-Moghadam et al, 2014, and lung tumors (Erfani-Moghadam et al, 2014), with superior efficiency and pharmacokinetics (Song et al, 2014). A different approach involves the employment of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] in a thin-layer evaporation methods for the preparation of CUR micelles able to treat ovarian Sarisozen et al, 2014) and colon (Abouzeid et al, 2013) cancer cells in vitro and in vivo (Abouzeid et al, 2013;Sarisozen et al, 2014), conferring synergistic effect to PTX- and DOX- (Abouzeid et al, 2013) based therapies.…”
Section: Polymeric Vesicular Systemsmentioning
confidence: 99%
“…94 In this regard, MCTS from MDR cell lines such as breast cancer MCF7/ Adr or ovarian cancer NCI-ADR-RES are useful tools to evaluate innovative solutions to restore DOX cytotoxicity as was shown with intrinsic drug-resistant glioblastoma U87MG cells. 70,71,[95][96][97][98] DOX-loaded nanoplatforms (targeted or nontargeted) that allow the simultaneous administration of several anticancer agents were evaluated in MCTS based on three criteria: accumulation, penetration and cytotoxic effects (Table 2). 70,71,[95][96][97][98] An excellent example of what can be done was the coloading of DOX with the MDR modulator curcumin (CUR) that inhibits different resistance-related pathways.…”
mentioning
confidence: 99%
“…70,71,[95][96][97][98] DOX-loaded nanoplatforms (targeted or nontargeted) that allow the simultaneous administration of several anticancer agents were evaluated in MCTS based on three criteria: accumulation, penetration and cytotoxic effects (Table 2). 70,71,[95][96][97][98] An excellent example of what can be done was the coloading of DOX with the MDR modulator curcumin (CUR) that inhibits different resistance-related pathways. 94,98 Polymeric micelles loaded with DOX and/or CUR (zeta potential of -4.4 mV, 15 nm in size) were decorated with a single-chain fragment variable (scFv), smaller, more stable and less immunogenic than IgG antibody, and were addressed against the GLUT1 protein in overexpressed glioblastoma cells.…”
mentioning
confidence: 99%
“…Bioadhesive pellets of hexylaminolevulinate (HAL) containing Carbopol 934 were developed by Hiorth et al [62] using a spheronization technique for photodynamic therapy of cervical cancer, and the prepared pellets were found to be mechanically stable with good bioadhesivity and proficient HAL release, thus proving to be an efficient therapy for cervical cancer. Moreover, Sarisozen et al [63] fabricated transferrin-modified polyethylene glycol phosphatidyl ethanolamine (PEG-PE)-based polymeric micelles for co-delivery of PTX and curcumin, which were assessed for cytotoxicity, cellular accumulation, and association against spheroids of multidrug-resistant ovarian cancer cells and in vivo tumor models using confocal imaging and flow cytometry. The results indicated that micelles penetrate significantly deeper in spheroids, delivering cytotoxic agents efficiently and thereby enhancing the cytotoxicity.…”
Section: Systemic Versus Localized Drug Delivery Systemsmentioning
confidence: 99%